Proceedings of the Ocean Drilling Program 1988
DOI: 10.2973/odp.proc.sr.103.180.1988
|View full text |Cite
|
Sign up to set email alerts
|

Drilling on the Galicia Margin: Retrospect and Prospect

Abstract: The principal findings of drilling on the Galicia margin during ODP Leg 103, supplemented by sampling from the submersible Nautile and calibration of seismic-reflection profiles, are:1. Peridotite, exposed in a ridge at the foot of the margin, is clinopyroxene-bearing spinel harzburgite, more than 90% serpentinized and cut by veins of calcite. During the rifting and lithospheric stretching stage of margin formation, these rocks ascended to the seafloor from a depth of about 30 km, where the temperature was abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
123
1

Year Published

1988
1988
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(131 citation statements)
references
References 17 publications
7
123
1
Order By: Relevance
“…The best studied of these margins is the West Iberian margin (Figure 1), which has been the subject of several drilling legs [Boillot and Winterer, 1988 Serpentinization also requires peridotites at appropriate temperature conditions. The maximum temperature at which serpentine can develop varies somewhat depending on the serpentine mineral under discussion and the study carried out.…”
Section: Introductionmentioning
confidence: 99%
“…The best studied of these margins is the West Iberian margin (Figure 1), which has been the subject of several drilling legs [Boillot and Winterer, 1988 Serpentinization also requires peridotites at appropriate temperature conditions. The maximum temperature at which serpentine can develop varies somewhat depending on the serpentine mineral under discussion and the study carried out.…”
Section: Introductionmentioning
confidence: 99%
“…We associate the change of tectonic style at this unconformityfrom a tectonically active to a passive mode-with a decline in stress regimes as the continental crust between Flemish Cap and Galicia Bank separated and seafloor spreading began in this region in the late Aptian. A similar unconformity can be identified on seismic data from Galicia Bank (Boillot, Winterer, et al, 1987), although the existence of this unconformity has not been confirmed by drilling. Site 641 on Galicia Bank penetrated this seismic horizon and found the strata to be conformable with no lacuna (Boillot, Winterer, et al, 1987).…”
Section: Tectonic Frameworkmentioning
confidence: 65%
“…A similar unconformity can be identified on seismic data from Galicia Bank (Boillot, Winterer, et al, 1987), although the existence of this unconformity has not been confirmed by drilling. Site 641 on Galicia Bank penetrated this seismic horizon and found the strata to be conformable with no lacuna (Boillot, Winterer, et al, 1987). The only change was lithologic, with an upward transition from conglomeratic and pebbly beds to shales across the seismic event.…”
Section: Tectonic Frameworkmentioning
confidence: 65%
See 2 more Smart Citations